Marxist Analysis of Capitalistic Trauma and Its Impact on Moral Degeneration After Industrial Revolution (Journal of Asian Development Studies, 2023)
The study's objective is to present a Marxist interpretation of American society as it is portrayed in Stephen Crane's Maggie: A Girl of the Streets. It was never going to be published because of its eccentricity. Additionally, the story shows the seedy side of life that is full of prostitution, sexual activity, and destitution; all of these things are shown in an unflattering way. Crane's portrayal of a population of impoverished Irish immigrants living in appalling conditions is a striking example of capitalist exploitation and poverty, with low wages, filthy living conditions, and an acute need for immoral activities to survive the harsh industrial revolution era. The work serves as an example of how capitalism and the decline of moral principles are intertwined. The study employs a sociological approach to examine the miserable circumstances of the characters in the novel's social background. A Marxist analysis of the current narrative underscores the detrimental effects of capitalistic monetization, including moral degradation and the dehumanizing effects of the capitalistic economic system. In order to evaluate the core data, the researcher used a qualitative descriptive approach. The supporting data, on the other hand, were gathered from books, papers, journals, internet sites, and other sources.